MtDNA differentiation and taxonomy of Central Asian racerunners of Eremias multiocellata-E. przewalskii species complex (Squamata, Lacertidae) - Orlova, Valentina F.; Poyarkov, Nikolay A. Jr.; Chirikova, Marina A.; Nazarov, Roman A.; Munkhbaatar, Munkhbayar; Munkhbayar, Khorlooghiyn; Terbish, Khayankhyarvagijn (Zootaxa, 2017)
We provide an integrative analysis of the diversity of the E. multiocellata—E. przewalskii species complex in Central and Middle Asia using morphological and molecular (COI DNA-barcoding) data. We report preliminary data on mtDNA variation within this group and clarify the taxonomic status and distribution of the members of the species complex. We also provide a description of a new Eremias species from Eastern Kazakhstan and western Mongolia, where it occurs in sympatry with E. multiocellata sensu stricto, from which it can be clearly differentiated using both morphological and molecular characters. The new species, described as Eremias dzungarica sp. nov., is assigned to the subgenus Pareremias on the basis of the following features: subocular not reaching mouth edge; one frontonasal; two supraoculars; the row of small granular scales between supraoculars and frontal with frontoparietals absent; distance between the femoral pore rows being wide; femoral pore rows not reaching knee-joint; coloration pattern with light colored ocelli with black edging. The new species can be distinguished from its congeners on the basis of the following morphological attributes: a medium-sized lacertid lizard, maximum snout-vent length (SVL) = 64.5 mm, tail being ca. 1.5 times longer than body length (SVL), hindlimbs relatively long (hindlimb length to SVL ratio 0.46); subocular scale not reaching mouth edge, in touch with 6–8 supralabials; males with bright coloration consisting of 2–3 dorsolateral rows of light-colored ocelli with thick black edging; the ventral row of ocelli in life is greenish to bluish; dorsal pattern consisting of black irregular blotches along the middorsal line. We also report on the high genetic and morphological diversity of E. multiocellata in Mongolia and China, synonymize E. m. bannikowi with the nominative form E. m. multiocellata, discuss variation within E. przewalskii, synonymize E. p. tuvensis with the nominative form E. przewalskii, provide new data on E. cf. reticulata and E. m. tsaganbogdensis, confirm validity and clarify distribution ranges of E. stummeri, E. szczerbaki and E. yarkandensis and discuss further progress on taxonomic studies of the E. multiocellata—E. przewalskii species complex.